0146 Managing Risk, The Use Of Simulation In Pharmacy Education. (1st November 2014) - Collins, Michael; Green, Alan; Maguire, Louise; Hardisty, Jessica; Scott, Lesley
Abstract : Background/context: Risk assessment and potential harm minimisation is paramount in healthcare (DoH 2006). An interactive lecture using simulation was designed to expose 140 third year pharmacy students to potentially life-threatening situations without risk to patients. The aim was student involvement in the decision-making processes associated with the prevention, recognition and management of opioid toxicity, in relation to analgesia prescription. Methodology: The pharmacy team aligned a case based scenario with learning outcomes of the session. The basis of this was Laerdal's "SimStore" for SimMan 3G resource package. The case was presented acknowledging the entry behaviour of students as having no prior experience or knowledge of the scenario we opted for lecture theatre real time delivery. Students acted as healthcare professionals, those remaining provided on-going support. Students reflected on the outcome and the scenario was replayed. Prior to formative feedback and facilitated consideration of the learning outcomes, students reflected on their learned experience. Results/outcomes: Integrating simulation in pharmacy education demonstrated the need for students to adopt a deep learning approach in enhancing understanding the role of the pharmacist in the context of multidisciplinary team work (Tsingos et al 2014). Student feedback on the learning experience was positive. Potential Impact: Curriculum development in relation to simulated practice for pharmacists provides a valuable opportunity to develop adaptive capacity and critical thinking skills in relation to their future role in patient safety in line with recommendations by The Chief Medical Officer (2009). References: Chief Medical Officer, (2009). Safer Medical Practice: Machines, Manikins and Polo Mints. London: DH Department of Health, (2006). Safety First: A report for patients, clinicians, and healthcare managers. London. DH Tsingos C, et al . "Reflective practice and its implications for pharmacy education". Am J Pharm Educ 2014;78(1):18.